1967
DOI: 10.1246/bcsj.40.97
|View full text |Cite
|
Sign up to set email alerts
|

The S. W. Polarographic Determination of Disulfide, Mercaptan and Free Sulfur in Petroleum Naphtha

Abstract: The application of square-wave polarography to the determination of small amounts of disulfide, mercaptan and free sulfur in a mixed solution of methanol, glacial acetic acid, and sodium acetate was studied. Disulfide, mercaptan, and free sulfur in concentrations below 10 ppm were easily determined in these mixed solvents. The derivative wave heights were proportional to the concentrations predicted by the theory of s. w. polarography. The effects of changes in solvent and in supporting electrolyte concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…A copper column was used for each sample to eliminate the interference of disulfides in voltammetric analyses [21]. The optimized parameters were: column diameter (0.5 cm), column height (18.0 cm), mass of copper (2.0 g), naphtha sample volume (2.0 mL) and flow of naphtha sample in the column (atmospheric pressure).…”
Section: Copper Column and Its Activation Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…A copper column was used for each sample to eliminate the interference of disulfides in voltammetric analyses [21]. The optimized parameters were: column diameter (0.5 cm), column height (18.0 cm), mass of copper (2.0 g), naphtha sample volume (2.0 mL) and flow of naphtha sample in the column (atmospheric pressure).…”
Section: Copper Column and Its Activation Proceduresmentioning
confidence: 99%
“…According to Table 1, Kashiki et al reported a methodology for quantifying elemental sulfur in naphtha samples using the same technique and working electrode employed in the proposed method [21]. The detection limit was found to be 0.5 mg L -1 .…”
Section: Limits Of Detection and Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] Fernandes et al 7 apresentaram a validação de uma metodologia usando a voltametria de onda quadrada (VOQ) para determinação S 0 em nafta com limites de detecção e quantificação de 0,003 mg L -1 e 0,009 mg L -1 , respectivamente, usando como eletrodo de trabalho o eletrodo de gota pendente de mercúrio (HMDE, do inglês: Hanging Mercury Drop Electrode) e como eletrólito suporte, uma solução tampão de ácido acético glacial 2 % (v/v) e acetato de sódio 1,4 mol L -1 em metanol. 8 Um trabalho anterior, utilizando o mesmo eletrólito de suporte e VOQ com eletrodo gotejante de mercúrio (DME, do inglês: Dropping Mercury Electrode) apresentou um limite de detecção de 0,5 mg L -1 . 9 Embora exista uma intolerância por parte da comunidade científica quanto ao uso do eletrodo de mercúrio, uma alternativa é o uso de eletrodos de filme de mercúrio (MFE, do inglês: Mercury Film Electrode).…”
Section: Introductionunclassified